Manifesty cyborgów: awangardowa wizja fuzji kobiety z maszyną (Hannah Höch — Giannina Censi — Mina Harker) - Mikołaj Marcela (Zagadnienia Rodzajów Literackich)
In Cyborg Manifesto Donna Haraway writes: “cyborgs (…) make very problematic the statuses of man or woman, human, artefact, member of a race, individual entity, or body”. This paper returns to the very beginning of thinking about this figure and examines the first protocyborg images created by Futurist and Dada female artists. I also look at Dracula’s Mina Harker as one of the first Western protocyborg figures. I ask to what extent such images anticipated the new forms of subjectivity and how they made the relation between human-nature and human-technology problematic as well as thinking in categories of gender.